PRAGMATIC AND SOCIOLINGUISTIC FACTORS IN COMPARATIVE TYPOLOGY (Web of Teachers: Inderscience Research, 2024)
This article explores the evolving scope of Comparative Typology, emphasizing its integration of Pragmatic and Sociolinguistic dimensions alongside traditional structural features such as phonology, morphology, and syntax. It highlights how Pragmatics, including speech acts, implicatures, deixis, and politeness strategies, interact with Sociolinguistics, which examines social norms, hierarchy, and cultural contexts. Drawing on cross-linguistic comparisons among English, Uzbek, and Russian, the article provides insights into universal and culture-specific patterns of language use. Key examples illustrate how languages manage social interaction, politeness, and implicature, revealing their embedded cultural and societal values. This interdisciplinary perspective underscores the relevance of Comparative Typology in understanding linguistic diversity and communicative norms.